Academic Senate Minutes 2004-02-05 - Academic Senate:::::::::
Approval of Agenda – item added: Request for Posthumous Degree for Kevin Patland – Approved. Minutes of 1/30/2020 – Approved. President Report. Provost Report. Vice Chair Report. Administration and Finance Report. Student Affairs Report. Associated Students Report. Staff Representative Report. Request for Posthumous Degree for Kevin Patland – approved by unanimous consent. Statewide Senators Report. Nominations for At-Large to Ex Com – voting result Amal Munayer. APARC Report. EPC Report. FSAC Report. SAC Report. Good of the Order.